Industry competition and fundamental analysis. (27th October 2016) - Safdar, Irfan
Abstract : Economic theory suggests that profits of firms in industries with higher competition are less persistent and more volatile than in industries with lower competition (Stigler, 1963; Mueller, 1977). Extending this reasoning, I hypothesize that accounting-based fundamentals are more effective in predicting performance in industries with lower competition. I find that a measure of fundamentals (Piotroski's F-score) has greater ability to identify potentially mispriced securities in industries with lower competition. The results are robust to using a variety of competition measures and imply that industry competition is an important consideration in the application of fundamental analysis.